Новый подход к синтезу семикарбазонов, тиосемикарбазонов и аминогуанидинов - Мухаметжанова С. К. Самал Клышбеговна; Штрыкова В. В. Виктория Викторовна; Куксёнок В. Ю. Вера Юрьевна; Филимонов В. Д. Виктор Дмитриевич (2014, 2014)
Заглавие с экрана